Start of the "Program for Improving Teaching in Higher Education in Ukraine": Review of the Ukrainian-British Forum "Excellence in Teaching and Learning in Higher Education" - Nataliia Boichenko (Філософія освіти, 2020)
The Ukrainian-British Forum "Excellence in Teaching and Learning in Higher Education" took place on December 4, 2020 in Kyiv and was dedicated to summarizing previous joint Ukrainian-British educational projects, including the Leadership Development Program of Ukrainian universities and the launch of the Higher Education Teaching Improvement Program Of Ukraine. The Forum was organized by the Institute of Higher Education of the National Academy of Pedagogical Sciences of Ukraine and the British Council in Ukraine. The Forum was attended by representatives of Ukrainian universities, Ukrainian educational top management and representatives of British analytical educational centers and NGOs to promote educational reforms. Emphasis was placed on taking the necessary concrete steps to establish a national platform for the exchange of experience in teaching and improving educational practices and the development of learning competencies between the British and Ukrainian sides. Nurturing the quality of higher education requires both the preservation of the national educational tradition in its best manifestations, and careful and careful adoption of world models of successful institutionalization of the experience of achieving high results in education. The improvement of standards of professional development of the main subjects of education in Ukraine should be a key factor for change at the next stage of educational reforms in Ukraine. Topics such as key stakeholders in education reform, institutional quality assurance of education, qualifications framework, expert experience, individual trajectory of teacher development, departure from the state-level diploma monopoly in Ukraine, etc. were also discussed. A significant expansion of opportunities for the creation of non-governmental – both private and branches of foreign higher education institutions in Ukraine – was announced. An important indicator of these changes should be the refusal from the monopoly of state-standard diplomas as evidence of higher education at the appropriate level.